Amalan penyoalan lisan guru kimia dalam pengajaran dan pembelajaran elektrokimia / Zanaton Haji Iksan - Zanaton, Iksan (2011)
Previous studies have revealed that students' understanding of various concepts of science is not always exact. Previous studies have also showed that teachers’ oral questioning practices are able to guide students' thinking and understanding of a scientific concept. Therefore, ineffective oral questioning could be one of the possible reasons for flawed understanding among students. Based on this, this study aims to explore the oral questioning practices of teachers in the teaching and learning of electrochemistry which is considered as a difficult topic. This study focused on the types of oral questions, strategies of oral questioning as well as to describe the emerging patterns of questioning practices during oral questioning. Data were collected through a qualitative approach that is non-participant observation and in-depth interviews. The participants of the study were five teachers who taught form four chemistry and were chosen through purposive sampling. The main finding showed that the types of oral questions by the five teachers can be divided into two main categories: content questions and management questions. The content questions can be further divided into five subcategories: relationship questions, process-based questions, comparing questions, observation questions and terminologybased questions. On the other hand, the management questions could be further categorized into four subcategories: pursuing questions, monitoring questions, encouraging questions and bilingual questions. Both content and management questions were complementary to each other and the simultaneous use of these two types of questions was needed in oral questioning during teaching. Exploration of questioning strategies during oral questioning has brought to light several key categories namely, dissemination of questions, waiting time, repetition and feedback in the teaching of electrochemistry. Dissemination of oral questions is first done openly to the whole, and when there is no response it is followed by focusing on certain students. Teachers provided a relatively long waiting time for the response of students. Low response from students is one of the reasons why questions are repeated. v Furthermore, the feedback provided by teachers is to ensure that the answers given are correct and in line with the objectives of teaching. The study noted that as the strategies of oral questioning arose from within the flow of questioning employed by the teachers, so the patterns of oral questioning would also be interesting to explore. The findings suggested that there are four patterns of oral questioning practiced by the teachers. The patterns were categorized as single questioning, separate questioning, continuous questioning and the expanding questioning. The single and separate questioning patterns do not emphasis on students’ prior knowledge. On the other hand, the continuous and expanding questioning patterns took into account students' prior knowledge by associating the students’ correct or incorrect responses. However, findings showed that teachers focused on the single and separate questioning patterns. This situation indicated that the oral questioning practices of the teachers were still at the low and medium cognitive levels. Several implications for teaching are discussed and some suggestions for further research are recommended.